2009
DOI: 10.4193/rhin08.126
|View full text |Cite
|
Sign up to set email alerts
|

Septoplasty outcome in patients with and without allergic rhinitis

Abstract: The surgeon should proceed with caution when managing patients with allergic rhinitis and nasal septum deviation. These patients are more likely to be less satisfied after septoplasty compared to patients without allergy. Adequate medical management of allergic rhinitis should be the first priority for these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 28 publications
6
47
1
4
Order By: Relevance
“…Indeed, the presence of nasal allergy was the only significant predictor of failure of surgical therapy in this series. These findings are consistent with earlier reports . On the one hand, this emphasises the importance of universally undertaken nasal allergy testing before surgery, and on the other hand, it raises an interesting question about the role and threshold for offering surgery to correct the structural component of nasal obstruction in patients with mucosal–structural disease.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the presence of nasal allergy was the only significant predictor of failure of surgical therapy in this series. These findings are consistent with earlier reports . On the one hand, this emphasises the importance of universally undertaken nasal allergy testing before surgery, and on the other hand, it raises an interesting question about the role and threshold for offering surgery to correct the structural component of nasal obstruction in patients with mucosal–structural disease.…”
Section: Discussionsupporting
confidence: 92%
“…The chi-square test showed a value of 9.075 with a p-value of 0.003 which had strong significance. The result is comparable to that of the study by Karatzanis AD et al 14 which showed that improvement after septoplasty was less in patients who were also having allergic rhinitis.…”
Section: Discussionsupporting
confidence: 81%
“…Inflammatory conditions like allergic rhinitis and chronic sinusitis lead to ETD and negative MEP. Studies by Karatzanis AD et al 14 and Rudmik L et al 15 showed that mere correction of DNS didn't have much effect on allergic rhinitis and chronic sinusitis respectively, and thereby on Eustachian tube function and MEP.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The presence of allergies also failed to show a relationship with outcomes in this study, despite its correlation with subjective satisfaction in 1 prior study. 8 There is some limitation in measurement of the severity of septal deviation. Classification used in this study, according to 1 of 3 categories using nasal endoscope, was not validated method.…”
Section: Discussionmentioning
confidence: 99%